Evaluation of psychiatric consultations requested for cancer patients hospitalized in a university hospital - Cansel, Neslihan; Unal, Ahmet (Annals of Medical Research, 2021)
Aim: Cancer is one the most important health problems of today. It is not just a medical and physical disease but a severe chronic condition with dispositional and social components. In our study, we aimed to analyze the diagnoses and treatments of oncologic inpatients whom were requested psychiatric consultations.Materials and Methods: 139 consulted patients of 828 inpatients who were hospitalized in Oncology and Radiation Department of Inonu University Faculty of Medicine, between January 1st, 2019 and February 27th, 2019 were included in the study. Sociodemographic data and examination findings of patients were obtained from electronic file records retrospectively. Results: The most common was gastric (14.9%); the second was breast (12.2%) and third was lung cancer. Depression was the most common psychiatric disease among these patients with 39.3% of women and 24% of men. The most preferred medications were escitalopram (35.4%) and quetiapine (20.8%).Conclusion: Physicians and other healthcare professionals responsible for the treatment of cancer patients should carefully evaluate these patients psychologically who may have the chance of getting psychiatric treatment only while hospitalized.